Adab Peserta Didik Menurut Abdullah Al Haddad - Wiguna, Bagus; Arsyad, Junaidi; Hanum, Azizah (TAWAZUN: Jurnal Pendidikan Islam, 2024)
This research aims to see Abdullah al-Haddad's role in education and his thoughts about student etiquette. This research uses qualitative methods with a library research approach. The data analysis process is carried out by reducing data, presenting data and drawing conclusions. The results of the research show that from Al-Haddad's perspective, students must have potential in terms of religious spirituality which is in line with Al-Haddad, that education is a way of seeking knowledge given by Allah SWT, knowledge is achieved by increasing devotion to Allah SWT and imitating the Prophet Muhammad in morals in the surrounding environment. Students' manners must also adapt to the Islamic education curriculum which consists of religious basics, philosophical basics, psychological basics and social basics. The educational methods according to Al-Haddad are Targhib (motivation), Tarim (forbid), Tahrij (distance yourself), and Uswah (exemplary). According to Al-Haddad, students must have good manners, good qualities and have good manners towards their teachers. Abstrak Penelitian ini bertujuan untuk melihat bagaimana peran Abdullah al-Haddad di dalam pendidikan dan pemikirannya tentang adab peserta didik. Penelitian ini menggunakan metode kualitatif dengan pendekatan kepustakaan (library research). Proses analisis data dilakukan dengan cara mereduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa dari perspektif Al-Haddad peserta didik harus memiliki potensi dalam segi spiritual keagamaan yang sejalan dengan Al-Haddad, bahwa pendidikan sebagai jalan menuntut ilmu yang diberikan Allah Swt., ilmu dicapai dengan semakin meningkatkan ketakwaan kepada Allah Swt. dan meneladani Rasulullah SAW dalam hal akhlak di lingkungan sekitar. Adab peserta didik juga harus menyesuaikan dengan kurikulum pendidikan Islam yang terdiri dari dasar agama, dasar falsafah, dasar psikologi dan dasar sosial. Adapun metode pendidikan menurut Al-Haddad yaitu Targhib (motivasi), Tarim (melarang), Tahrij (menjauhkan diri), dan Uswah (keteladanan). Peserta didik menurut Al-Haddad haruslah memiliki adab yang baik, sifat-sifat yang baik dan mempunyai adab kepada gurunya